2014
DOI: 10.1186/s13062-014-0028-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular complementarity between simple, universal molecules and ions limited phenotype space in the precursors of cells

Abstract: BackgroundFundamental problems faced by the protocells and their modern descendants include how to go from one phenotypic state to another; escape from a basin of attraction in the space of phenotypes; reconcile conflicting growth and survival strategies (and thereby live on ‘the scales of equilibria’); and create a coherent, reproducible phenotype from a multitude of constituents.Presentation of the hypothesisThe solutions to these problems are likely to be found with the organic and inorganic molecules and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 138 publications
0
20
0
Order By: Relevance
“…Polyphosphates (polyP) are prebiotic polymers (132): highly conserved, universal and structurally extremely simple. They exist as long, typically unbranched chains of phosphoanhydride bond-linked phosphates, which can reach lengths of up to 1000 P i units (133).…”
Section: Polyphosphate: a Protein-like Inorganic Chaperonementioning
confidence: 99%
“…Polyphosphates (polyP) are prebiotic polymers (132): highly conserved, universal and structurally extremely simple. They exist as long, typically unbranched chains of phosphoanhydride bond-linked phosphates, which can reach lengths of up to 1000 P i units (133).…”
Section: Polyphosphate: a Protein-like Inorganic Chaperonementioning
confidence: 99%
“…One approach is to focus on those unifying problems that recur in different fields, for example, how to limit the enormity of phenotype space so that Darwinian selection can act ( Kauffman, 1996 ). To solve this problem, we have invoked a key role for simple, universal molecules and inorganic ions, termed SUMIs, which include polyphosphate, polyhydroxybutyrate, polyamines, and calcium ( Norris et al, 2015 ). A complementary approach is to ask whether the paradigm would help elucidate another field, for example, could a hypothesis developed for the origins of life help with cell division?…”
Section: Discussionmentioning
confidence: 99%
“…In the latter case, accumulation of cardiolipin would be an attractive candidate given its roles in initiation of replication ( Sekimizu and Kornberg, 1988 ; Makise et al, 2002 ) and in cell division ( Mileykovskaya and Dowhan, 2000 ; Koppelman et al, 2001 ; Kawai et al, 2004 ). Finally, there are molecules of major physiological importance that are often overlooked ( Norris et al, 2015 ); these include polyphosphate which, in some bacteria, has been shown to play a role in the cell cycle ( Boutte et al, 2012 ) and to exist in both soluble and insoluble forms ( Klauth et al, 2006 ).…”
Section: Intensity Sensing and Quantity Sensingmentioning
confidence: 99%
“…An importance of polyP for the proper function of the mitochondrial NAD kinase [21,22] has been shown, which potentially affects the total mitochondrial metabolism. The role of polyP as an energy source for the ATPase has been already discussed [23]. However, there are still a large number of open questions concerning the role of polyP in energy metabolism [23]: (a) it is still not clear whether polyP could act as an energy molecule in mammalian cells, being utilized in the various types of ATPases; (b) how is polyP produced or elongated in mitochondria and how this polymer affects mitochondrial respiration and ultimately oxidative phosphorylation.…”
Section: Introductionmentioning
confidence: 99%